Slow Tourism as a Tourism Alternative to Sustainable Development - SOUSA, Bruno; SANTOS, Rossana; LUBOWIECKI-VIKUK, Adrian (Journal of Environmental Management and Tourism, 2021)
Sustainability is a topic that is currently being discussed and constantly adapting, since it is related not only to an ecologically correct posture and strategy but also economically viable and socially equitable. Therefore, the importance given by the media to the theme of ecology, sustainability has led to a growing concern among the population. In this context, slow tourism is based on the concept of speed. It involves traveling for a prolonged period at a slow pace, allowing the tourist a deep, authentic, and cultural experience. This paper presents theoretical considerations that aim to understand how “slow tourism” can become a destination for future sustainable tourism trips